Simultaneous multi‐slice combined with PROPELLER. Issue 2 (19th December 2017) - Norbeck, Ola; Avventi, Enrico; Engström, Mathias; Rydén, Henric; Skare, Stefan
Abstract : Purpose: Simultaneous multi‐slice (SMS) imaging is an advantageous method for accelerating MRI scans, allowing reduced scan time, increased slice coverage, or high temporal resolution with limited image quality penalties. In this work we combine the advantages of SMS acceleration with the motion correction and artifact reduction capabilities of the PROPELLER technique. Methods: A PROPELLER sequence was developed with support for CAIPIRINHA and phase optimized multiband radio frequency pulses. To minimize the time spent on acquiring calibration data, both in‐plane‐generalized autocalibrating partial parallel acquisition (GRAPPA) and slice‐GRAPPA weights for all PROPELLER blade angles were calibrated on a single fully sampled PROPELLER blade volume. Therefore, the proposed acquisition included a single fully sampled blade volume, with the remaining blades accelerated in both the phase and slice encoding directions without additional auto calibrating signal lines. Comparison to 3D RARE was performed as well as demonstration of 3D motion correction performance on the SMS PROPELLER data. Results: We show that PROPELLER acquisitions can be efficiently accelerated with SMS using a short embedded calibration. The potential in combining these two techniques was demonstrated with a high quality 1.0 × 1.0 × 1.0 mm 3 resolution T2 ‐weighted volume, free from banding artifacts, and capable of 3D retrospective motion correction, with higher effective resolution compared to 3D RARE. Conclusion: With the combination of SMS acceleration and PROPELLER imaging, thin‐sliced reformattable T2 ‐weighted image volumes with 3D retrospective motion correction capabilities can be rapidly acquired with low sensitivity to flow and head motion. Magn Reson Med 80:496–506, 2018. © 2017 International Society for Magnetic Resonance in Medicine.